PERAN HAKIM DALAM MEWUJUDKAN PERLINDUNGAN HUKUM AHLI WARIS MELALUI PUTUSAN BERBASIS AKTA PERDAMAIAN DI PENGADILAN AGAMA SUKABUMI - Solihin; Utang Rosidin; Iwan Setiawan (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2026)
The settlement of inheritance disputes through a peace deed is an alternative that is widely applied in religious courts because it can maintain family relations and provide a more peaceful settlement. However, the agreement of the parties needs to be supervised by a judge so as not to conflict with Islamic inheritance law, the Compilation of Islamic Law, and the principle of legal protection. This study aims to analyse the role of judges in ensuring the legal protection of heirs through a peace deed-based decision at the Sukabumi Religious Court, examine the judge's legal considerations, and analyse the juridical and sociological implications of the decision. The research uses an empirical juridical method with a qualitative approach through the analysis of Decision Number 713/Pdt.G/2023/PA. Smi, Number 561/Pdt.G/2023/PA. Smi, and Number 517/Pdt.G/2024/PA. Smi, as well as interviews with judges and mediators. The results of the study show that judges play the role of peace facilitators, supervisors of the legality of agreements, and protectors of the rights of heirs. The judge's consideration is based on legality, substantive justice, utility, and legal protection so that a peace deed-based decision provides legal certainty, executory power, and supports fair and benefit-oriented dispute resolution.